2014
DOI: 10.3109/08820139.2014.932378
|View full text |Cite
|
Sign up to set email alerts
|

Anti-C1q in chronic hepatitis C Virus genotype IV infection: association with autoimmune rheumatologic manifestations

Abstract: A growing body of evidence suggests that anti-complement-1q (anti-C1q) antibodies are elevated in a variety of autoimmune disease. Therefore, we investigated their prevalence and clinical significance in plasma of patients with hepatitis C virus (HCV) genotype IV in the presence and absence of autoimmune extra hepatic manifestations in comparison to normal healthy individuals. Plasma Anti-C1q Abs levels were assessed by an Enzyme Linked Immunosorbant Assay in 91 chronic HCV-infected patients (51 with and 40 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Although the C1q is a major component of HCV-induced cryoprecipitate, to the best of our knowledge there are no published studies addressing this issue. Low levels of C1q and a significant prevalence of anti-C1q autoantibodies are shared features of SLE and HCV-induced cryoglobulinemia ( 36 , 73 , 102 , 103 ).…”
Section: Apoptotic Role Of C1q In Slementioning
confidence: 99%
“…Although the C1q is a major component of HCV-induced cryoprecipitate, to the best of our knowledge there are no published studies addressing this issue. Low levels of C1q and a significant prevalence of anti-C1q autoantibodies are shared features of SLE and HCV-induced cryoglobulinemia ( 36 , 73 , 102 , 103 ).…”
Section: Apoptotic Role Of C1q In Slementioning
confidence: 99%
“…The immune responses are highly complex and not well defined. Extrahepatic autoimmune involvement with abnormal immune responses mediated by both T and B lymphocytes is observed in CHC, mainly in those with cryoglobulinemia [ 21 , 22 ]. Nevertheless, the role of different IL-17A-secreting T cells on CHC patients with MC is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study demonstrated a higher prevalence of anti-C1q autoantibodies among patients with HCV and rheumatologic manifestations, compared to patients with HCV without these manifestations. This study also demonstrated an increased prevalence of anti-C1q autoantibodies in patients infected with HCV with mixed cryoglobulinemia and lymphoma, opening the possibility of their use as a biomarker for the diagnosis of lymphoma [38].…”
Section: Hepatitis Cmentioning
confidence: 99%